Implementation of Government Accounting Standards, Its Implications for Accountability and Transparency in Indonesian Local Governments - Kurniawan, Agus; Etika, Citra (Jurnal Kajian Akuntansi, Auditing dan Perpajakan, 2026)
This study analyzes how the implementation of Government Accounting Standards (SAP) is associated with accountability and transparency in Indonesian local government financial reporting. A descriptive mixed-method design was applied. Quantitative evidence was derived from document analysis of audited 2023 Local Government Financial Statements (LKPD) from 15 city governments. Qualitative evidence was obtained from a survey of financial officers regarding implementation barriers. SAP implementation was operationalized through a normalized compliance index based on accuracy, completeness, timeliness, and transparency of disclosure. The findings show clear variation across local governments. Higher scores appear in governments with stronger staff capacity, more integrated information systems, and more active internal oversight. Lower scores are associated with limited technical training, fragmented data systems, and delays in report consolidation. The results indicate that formal adoption of SAP alone is not sufficient to produce accountable and transparent reporting. Implementation quality depends on organizational capacity and monitoring arrangements. This study contributes by combining compliance scoring with field-based perceptions of implementation barriers in one analytical frame and offers practical implications for training, digitalization, and audit follow-up.